Remagnetization of Permian Emeishan basalts: Constraints on the timing of native copper mineralization in northeast Yunnan Province, China - Liu, Chengying; Paterson, Greig A.; Li, Shihu; Pan, Yongxin; Zhu, Rixiang (Frontiers in Earth Science, 2021)
New paleomagnetic results are reported from the Permian Emeishan basalts in the Zhaotong area, NE Yunnan province, China. Detailed stepwise thermal demagnetization on basaltic samples from 16 sites from the Dadi section, which represent basalt units III and IV, isolated two groups of characteristic remanent magnetizations. Samples in unit IV (5 sites) record a southwestward declination and a moderate downward inclination that is considered to be a partial remagnetized remanence. The bottom flows from unit III (11 sites) record a normal polarity direction, interpreted as a remagnetization, which yields a tilt-corrected mean direction of Ds/Is = 8.8/31.6° (N = 9, ks = 39.7, α95 = 8.3°), with a corresponding paleomagnetic pole at 77.1°N, 240.0°E (K = 49.2, A95 = 7.4°). The remagnetized directions have steeper inclinations than the primary directions that have been successfully recovered from other studies in this area of the Emeishan basalts. By comparison with the Phanerozoic paleomagnetic poles of the South China Block, the preferred timing of remagnetization is the Lower-Middle Jurassic. Field relationships suggest that the remagnetization of the Emeishan basalts is coeval with the spatially related, but localized, copper mineralization. Thus the timing of the main copper mineralization hosted in the Emeishan basalts is proposed to occur in the Lower-Middle Jurassic. The extent of the copper mineralization and hence the remagnetization of the Emeishan basalts is highly dispersed and controlled by small scale structural and lithological features, which suggests that it is a localized phenomenon.